An Improved King–Werner-Type Method Based on Cubic Interpolation: Convergence Analysis and Complex Dynamics - Moin-ud-Din Junjua; Ibraheem M. Alsulami; Amer Alsulami; Sangeeta Kumari (Axioms)
In this paper, we study the convergence and complex dynamics of a novel higher-order multipoint iteration scheme to solve nonlinear equations. The approach is based upon utilizing cubic interpolation in the second step of the King–Werner method to improve its convergence order from <semantics>2.414</semantics> to 3 and the efficiency index from <semantics>1.554</semantics> to <semantics>1.732</semantics>, which is higher than the efficiency of optimal fourth- and eighth-order iterative schemes. The proposed method is validated through numerical and dynamic experiments concerning the absolute error, approximated computational order, regions of convergence, and CPU time (sec) on the real-world problems, including Kepler’s equation, isentropic supersonic flow, and law of population growth, demonstrating superior performance compared to some existing well-known methods. Commonly, regions of convergence of iterative methods are investigated and compared by plotting attractor basins of iteration schemes in the complex plane on polynomial functions of the type <semantics>zn−1</semantics>. However, in this paper, the attractor basins of the proposed method are investigated on diverse nonlinear functions. The proposed scheme creates portraits of basins of attraction faster with wider convergence areas outperforming existing well-known iteration schemes.